التأويل والقراءة التأويلية - بعدا ش, ناصر (University of El-oued, 2020)
لخص. تحاول هذه الورقة اإلجابة عن بعض األسئلة املتعلقة بتحديدد وضدبب بعدض املفداهيم املتعلقدة بالتأويل والقراءة التأويلية ومفهوم تعدد الدالالت، ومستويات كل منهما، وكذا الحدود الفارقة بين املصطلحات النقدية مثل التحليل والتفسير، ومفهوم التلقي، وهي مفاهيم شاع تداولها على نطاق واسع في هذا العصر، وما ذلك إال ألهمية عنصر القراءة في الحياة األدبية والنقدية، وهدي القد دراءة التد د تترد داوال الحد دروف وصد دوال إعد دى املعد داني مد دع قد ددر ها علد دى تأويد دل املضددمر وكشدد الخفددي، وبالتاعي فالقراءة العميقة الناقدة تتضمن الفهم املباشر للنص املقروء الذي يشتمل التعرف على معداني بعدض التلمدات املتضدمنة لهدذا الدنص، وليدتم بعدد ذلدك القيدام بعمليدة أ در هدي تفسدير املقروء، وذلك بالتوصل إعى فهم شامل للنص ومحاولة التوصدل إعدى الددالالت و املعداني الخفيدة، ومنه : - ما الغاية املرجوة من القراءة التأويلية ؟ ومن هدو املتلقدي الدذي يقدوم بقدراءة النصدو األدبية ويتفاعل معها، ويعطيها حقها من التأويل؟ - وما الدافع إعى التأويل،أهو الغموض ؟ أم ذلك التعقيد اللفظي واملعنوي في النص ؟ - هل للقراءة دوال في انتاج املعنى؟ Abstract: This paper attempts to answer some questions related to the definition and control of some concepts related to interpretation and hermeneutics, the concept of multiplicity of connotations, the levels of each, as well as the differences between critical terms such as analysis and interpretation, and the concept of receiving. These concepts are widely circulated in this era, and only because of the importance of the element of reading in literary and critical life, a reading that goes beyond the letters to the meanings with its ability to interpret the track and reveal the hidden, and therefore a deep critical reading includes a direct understanding of the readable text, which includes recognition On the meanings of some of the words included in this text, and then to do another process is the interpretation of the reader, by reaching a comprehensive understanding of the text and trying to reach the semantics and meanings, including: - What is the purpose of interpretive reading? Who is the recipient who reads literary texts and interacts with them, and gives them the right of interpretation? What is the motive for interpretation, is it ambiguity? Or that verbal and moral complexity in the text? - Do you read countries in the production of meaning?
مقال. Ex Professo. مج5. ع.1. جامعة الوادي
Keywords: االكلمات المفتاحية: القراءة، القارئ، التأويل، املستو ، تعدد الدالة.; Keywords: reading, reader, hermeneutics, level, multiplicity of significance.